BIO MEDICAL WASTE MANAGEMENT - Suresh Ramamurthy,; Shwetha Madhusudhanan,; Suman Vilasini, (International Journal of Innovations in Engineering Research and Technology, 2021)
The main purpose of this research is to identify the quantum of the medical waste generated and various methods involved in their disposal. The Indian Government has introduced Bio medical rules and its amendments in 2016 which dictate effective management of waste to prevent the diseases. These wastes have to be collected, segregated and then transported to the common bio medical waste treatment centre or if possible can be reduced at the source itself minimizing the quantity. It should not be dumped, landfilled, mixed with other municipal solid waste thereby creating a menace to the general public. If possible, it is to be considered for recycling or reuse in case of plastic medical waste.The study discusses about the quantity of waste collected in the 4 colour code categories namely yellow, red, blue and white. It also checks whether proper collection and disposal methods are followed thus creating awareness in the management of waste.